Molecular signalling of a novel curcumin derivative versus Tadalafil in erectile dysfunction. (25th July 2014) - Abdel Aziz, M. T.; Rezq, A. M.; Atta, H. M.; Fouad, H.; Zaahkouk, A. M.; Ahmed, H. H.; Sabry, D.; Yehia, H. M.
Summary The efficacy of a novel curcumin derivative (NCD) versus tadalafil in erectile signalling was assessed. Ten control male rats and 50 diabetic male rats were used and divided into the following: diabetic (DM), curcumin (CURC), NCD, tadalafil and NCD combined with tadalafil rat groups. Cavernous tissue gene expression of heme oxygenase‐1 (HO‐1), Nrf2, NF‐B and p38, enzyme activities of heme oxygenase (HO) and nitric oxide synthase (NOS), cGMP and intracavernosal pressure (ICP)/mean arterial pressure (MAP) were assessed. Results showed that 12 weeks after induction of diabetes, erectile dysfunction (ED) was confirmed by the significant decrease in ICP/MAP, a significant decrease in cGMP, NOS, HO enzyme activities, a significant decrease in HO‐1 gene and a significant increase in NF‐Ҡβ, p38 genes. Administration of all therapeutic interventions led to a significant increase in ICP/MAP, cGMP levels, a significant increase in HO‐1 and NOS enzymes, a significant increase in HO‐1, and Nrf2 gene expression, and a significant decrease in NF‐Ҡβ, p38 gene expression. NCD or its combination with tadalafil showed significant superiority and more prolonged duration of action. In conclusion, a tendency was observed that CURC and NCD have high efficacy and more prolonged duration of action in enhancing erectile function.